Ferroptosis-related long noncoding RNA signature predicts the prognosis of clear cell renal cell carcinoma / Liu Jiawen - Liu , Jiawen (2022)
Clear Cell Renal Cell Carcinoma (ccRCC) is very common and accounts for most kidney cancer deaths. While many studies are being conducted in finding the prognosis signatures of ccRCC, we believe that ferroptosis, that involves programmed cell death dependent on iron accumulation has therapeutic potential in ccRCC. Recent research showed that long noncoding RNAs (lncRNAs) have been shown to be involved in ferroptosis-related tumor processes and are closely related to survival in patients with ccRCC. Hence in this study we aim to further explore the role of ferroptosis-related lncRNAs (FRLs) in ccRCC, hoping to establish a signature to predict the survival outcome of ccRCC. Here we analyzed transcriptome data from The Cancer Genome Atlas database (TCGA) and ferroptosis-related genes (FRGs) from FerrDb to identify FRLs using Pearson’s correlation. Lasso Cox regression analysis and multivariate Cox proportional hazards models screened seventeen optimal FRLs for developing prognostic signatures. Kaplan–Meier survival curves and receiver operating characteristic (ROC) curves were then plotted for validating the sensitivity, specificity, and accuracy of the identified signatures. CIBERSORT algorithm were deployed to explore the role of these FRLs in tumor microenvironment (TME). It was concluded that these models demonstrate excellent performance in predicting prognosis among patients with ccRCC and which also indicated association with the clinicopathologic parameters such as tumor grade, tumor stage and tumor immune infiltration. In conclusion, our findings provide novel insights into ferroptosis-related lncRNAs in ccRCC which are important targets for investigating the tumorigenesis of ccRCC.